LITURGI SEBAGAI MODEL BERPASTORAL - Epafras Mario Lumunder; Tifany Fergie Tombokan; Samuel Wailan Leonard Wanget (Institut Agama Kristen Negeri Manado, 2023)
Liturgy, often thought of as simply the manner of worship, actually has a broader meaning. From the Greek, liturgy comes from